1979
DOI: 10.1159/000460473
|View full text |Cite
|
Sign up to set email alerts
|

Improved Yields of Factor VIII from Heparinized Plasma

Abstract: The Factor VIII procoagulant activity in plasma, cryoprecipitate, and their polyethylene glycol (PEG) precipitates is markedly increased if blood is collected into heparin rather than into citrate phosphate dextrose (CPD). There is a 34% increase in the initial level of the Factor VIII activity in the heparinized plasma with 78% of this initial activity (184 U) recovered in the cryoprecipitate. As well, the stability of the Factor VIII activity is improved: after 24 h of incubation at 22°C, 99% of the initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 7 publications
4
18
0
Order By: Relevance
“…This is consistent with reports that factor VIII is a calcium-linked protein complex [36,37] and with the findings of others who have studied the stability of VIITC in plasma [13,14,38,39,40], While the importance of ionised calcium to VIII:C stability in plasma is well docu mented its relevance during the preparation of factor VIII concentrates has not been fully appreciated, possibly because the effects may not be seen with small-scale preparations or in typical bench-top experiments, where finishing procedures are completed fairly quickly or may be omitted altogether.…”
Section: Calcium Addition In Full-scale Experimentssupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with reports that factor VIII is a calcium-linked protein complex [36,37] and with the findings of others who have studied the stability of VIITC in plasma [13,14,38,39,40], While the importance of ionised calcium to VIII:C stability in plasma is well docu mented its relevance during the preparation of factor VIII concentrates has not been fully appreciated, possibly because the effects may not be seen with small-scale preparations or in typical bench-top experiments, where finishing procedures are completed fairly quickly or may be omitted altogether.…”
Section: Calcium Addition In Full-scale Experimentssupporting
confidence: 93%
“…Results from the preliminary study suggested that the loss of VIII:C activity previously observed over product finishing [4] might be almost fully explained by a citrateinduced inactivation of VIII:C. Similar inactivation behaviour had been observed in plasma [13,14] with one suggestion being that the presence of calcium ions is essential for VIILC stability. Therefore a number of for mulations were examined in which the concentration of ionised calcium was controlled by the addition of calcium chloride to factor VIII solutions at different citrate con centrations.…”
Section: Comparison Of Different Formulationssupporting
confidence: 61%
“…These results have been substantiated by others [4,5]. We [2] and Morgenthaler et al [4] have also found that heparin, added to citrate plasma or when used as a pri mary anticoagulant, significantly stabilizes FVIII so that a two-phase decay does not occur.…”
supporting
confidence: 70%
“…In these experiments they concluded that CPD gives the highest yield of FVIII. We have previously reported that the FVIII level is considerably higher in heparinized plasma rather than citrated plasma with average values of 1.3 U/ml in heparin compared to 1.0 U/ml in citrate [2,3]. These results have been substantiated by others [4,5].…”
mentioning
confidence: 55%
“…After centrifugation [24], the pellets were resolubilized at 37 "C with buffer A [25 mM sodium acetate, 0.9% w/v NaCl, 8 units/ml heparin, 0.8 pM phenylalanyl-prolyl-arginine chloromethane (Phe-Pro-ArgCH2C1) pH 6.51. The resolubilized cryoprecipitates were then pooled and fractionated further by addition of poly(ethyleneglyco1) (4000) to 4.0% (w/v) and to 11 % (w/v) essentially as described previously [22]. The 11% precipitate was resuspended in equal volumes of heparinized saline (0.9% NaC1, 4 units/ml heparin, 10% glycerol 0.8 pM Phe-Pro-ArgCH,Cl), and buffer B (100 mM sodium acetate, 1 M lysine, pH 6.5).…”
Section: Preparation Effactor Vzzimentioning
confidence: 99%